Methodological framework of the electoral integrity model - Vélez Valdés, Alberto (Politikon: The IAPSS Journal of Political Science, 2016)
This research note discusses the methodological framework of the electoral integrity model, specifically the weaknesses and strengths of the Perception of Electoral Integrity Index in its 2013 and 2014 versions. It explains the theoretical concept and the importance of measure both electoral integrity and electoral malpractices. Furthermore, emphasizes on some technical aspects related with the robustness of the ranking, the possible sources of bias in the expert surveys as well as the internal and external consistency of the findings. To give a suggestion for improving the model, it provides some adjustments. Finally, it gives a conclusion about the future of the project and the usefulness for the democratization of its knowledge built.